(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This research work presents an analysis of the formation of winter wheat yield depending on irrigation methods and irrigation regimes in the cultivation of winter wheat varieties in the conditions of irrigated light gray soils of the Kashkadarya region. According to the average 3-year results obtained during 2022-2024, the yield of winter wheat varieties ranged from 44.3 c/ha to 74.0 c/ha, and it was established that the yield of winter wheat varieties was higher when irrigating with sprinkler irrigation, with an irrigation regime of 70-75-65% of LFC before irrigation